A Lyapunov inequality for monotone quasilinear operators - de Napoli, Pablo Luis (2005)
In this work we prove a Lyapunov-type inequality for monotone quasilinear operators generalizing the p−Laplacian. This inequality enable us to obtain lower bounds for the first eigenvalue obtained in the setting of Orlicz-Sobolev spaces.